Profile and outcome of atypical progressive acute kidney injury in children in a tertiary care hospital in Indonesia - Fitria, Fitria; Sovira, Nora; Haris, Syafruddin; Yusuf, Sulaiman; Herdata, Heru Noviat; Ismy, Jufitriani (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2026)
Background: Atypical progressive acute kidney injury (APAKI) in children is a severe form of acute kidney injury (AKI) marked by rapid progression to end-stage and high mortality. Since August 2022, Indonesia has reported a surge of pediatric AKI, predominantly in previously healthy children, linked to contamination of syrup medications with diethylene glycol (DEG) and ethylene glycol (EG).Objective: The objective of this research is to identify the characteristics and clinical outcomes of children with APAKI at Dr. Zainoel Abidin Hospital in Banda Aceh, a tertiary care hospital in Indonesia.Methods: This analytical observational study used secondary data from pediatric medical records of APAKI cases between June and December 2022. A total sampling technique identified 31 eligible patients aged 1–18 years old. Clinical characteristics, laboratory parameters, and outcomes were analyzed using descriptive statistics and Fisher’s Exact tests.Results: Thirty-one pediatric patients with APAKI are included; most are male (64.5%), aged 1–5 years (93.5%), domiciled outside Banda Aceh (58.1%), and had good nutritional status (80.6%). The mortality is high (74.2%). Genitourinary symptoms such as oliguria/anuria are the most frequent (87.1%), and dialysis is the main therapy (64.5%). Poor outcomes are significantly associated with respiratory symptoms (OR=16; 95%CI: 1.643-155.77), PELOD-2 score ≥10 (OR=10.89; 95%CI: 1.140-103.98), and mechanical ventilation (OR=16; 95%CI: 1.643-155.77). Laboratory predictors of mortality included leukocytosis (OR=11.11; 95%CI: 1.701-72.564), thrombocytopenia (OR=1.90; 95%CI: 1.207-2.957), elevated urea (OR=13.2; 95%CI: 1.124-154.920), elevated creatinine (OR=36.67; 95%CI: 3.124-430.333), reduced eGFR (OR=22; 95%CI: 1.924-251.539), and elevated SGOT (OR=22; 95%CI: 1.924-251.539) and SGPT (OR=36.67; 95%CI: 3.124-430.333). Toxicology testing is correlated with better survival (OR=0.07; 95% CI: 0.006-0.889).Conclusion: APAKI in children is associated with high mortality. Poor outcomes are strongly linked to respiratory involvement, high PELOD-2 scores, mechanical ventilation, and multiple laboratory abnormalities, highlighting the importance of early risk identification and timely management.